A Skills-Based Human Capital Framework to Understand the Phenomenon of Youth Economic Disengagement - Angel-Urdinola, Diego F. (World Bank, Washington, DC, 2018)
This paper revisits traditional human capital models and proposes a new conceptual framework of human capital accumulation, anchored in skills development, to illustrate the phenomenon and implications of youth economic disengagement. In the framework, youth economic disengagement is defined as a state (temporary or permanent) where individuals stop accumulating human capital due to inadequate access and quality of opportunities for skills development through formal education and employment. Total economic disengagement is a rational choice that individuals make when (i) the formal education system and labor market do not contribute to build skills that are valued by the labor market, and (ii) the costs related to economic engagement (that is, studying and working) surpass its benefits. The phenomenon of economic disengagement has lifelong implications that not only constrain and restrain future earnings, but also undermine prospects for improvements in productivity and economic growth.